Pathways from Jobs to Social Cohesion - Wietzke, Frank-Borge (Oxford University Press on behalf of the World Bank, 2016)
There is growing recognition that access to good jobs is an important driver of social cohesion. Although the economic dimensions of labor market outcomes are relatively well documented, evidence on the link between social cohesion and jobs is still surprisingly scarce. This paper, based on an earlier background report for the WDR 2013, presents empirical evidence for pathways between labor market outcomes and social cohesion. The findings indicate that formal employment is associated with a range of social outcomes and behaviors that are typically associated with higher levels of social cohesion. However, there are also indications that this relationship varies across dimensions of social wellbeing. In particular, social interactions and political activism among those in regular employment can either improve the quality of aggregate institutions or deepen existing social divides.